Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.2198/jelectroph.53.1
|View full text |Cite
|
Sign up to set email alerts
|

Glycoproteomic analysis of abnormal N-glycosylation on the kappa chain of cryocrystalglobulin in a patient of multiple myeloma

Abstract: SUMMARYCrystalglobulinemia (cryocrystalglobulinemia) is a rare complication of multiple myeloma. Crystallization of immunoglobulin in blood circulation causes systemic vasculopathy especially in skin and kidney. We found a rare case of crystalglobulinemia in which the light chain was N-glycosylated. The abnormal N-glycosylation was primarily detected as the molecular mass shift on SDS-PAGE by PNGase F treatment. The cryocrystalglobulin was shown to be composed of 55-kDa heavy and 32-kDa light chains on SDS-PAG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…However, similar to our study, they also noted higher variation in sialylation level among patients with active myeloma when compared to healthy control. Sialylated glycans located on the IgG light chain and an increase in its molecular weight in SDS-PAGE have been previously reported in multiple myeloma and associated with spontaneous precipitation . We found heavier light chains in patients MM1, MM2, MM5, REL3, MGUS4, and MGUS6 with all samples but MM2 being of the lambda subtype.…”
Section: Discussionsupporting
confidence: 69%
“…However, similar to our study, they also noted higher variation in sialylation level among patients with active myeloma when compared to healthy control. Sialylated glycans located on the IgG light chain and an increase in its molecular weight in SDS-PAGE have been previously reported in multiple myeloma and associated with spontaneous precipitation . We found heavier light chains in patients MM1, MM2, MM5, REL3, MGUS4, and MGUS6 with all samples but MM2 being of the lambda subtype.…”
Section: Discussionsupporting
confidence: 69%
“…Nonfucosylated oligosaccharides on the κ chain of crystalglobulins, which lead to protein misfolding and insolubility of immunoglobulin, have been suggested. [ 9 , 10 ] In cases of crystalglobulinemia, despite negative findings of cryoglobulins and cryofibrinogens according to routine laboratory studies, cryoprecipitates can be observed grossly in blood collection tubes or microscopically in blood smears. Microscopic detection of irreversible cryoprecipitation and the presence of intravascular crystalized bodies in affected tissues in pathological specimens are critical for the diagnosis of crystalglobulinemia.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cylinder-like bodies were found in deep organs that are not affected by external temperature. It has been reported that glycosylation of an N-terminal residue of the immunoglobulin light chain is related to crystallization (11,19).…”
Section: Discussionmentioning
confidence: 99%